Development of a Procedure for Determining the Pre-Failure Condition of the Axle Boxes of Railway Rolling Stock - Igor Martynov; Juraj Gerlici; Alyona Trufanova; Vadim Petuhov; Vadim Shovkun; Kateryna Kravchenko (Communications - Scientific letters of the University of Zilina, 2022)
It has been determined that the greatest risk of an error in determining the technical condition of the axle box unit in the so-called "zone of uncertainty" is in the impossibility of unambiguously assessing its technical condition. To solve this problem, a model is proposed in the form of an n-dimensional radius vector, which has a direction towards an increase in the probability of failure and a deterioration in its parameters’ values. Such a model for determining the axle box unit’s pre-failure condition will reduce the risk of errors in decision-making.